Pengaruh Literasi Halal, Sertifikasi Halal, Ingredients, dan Kualitas Produk Terhadap Keputusan Pembelian pada Produk Food and Beverage di Kompleks Wisata Yogyakarta - Gita Nika, Dila; Kamal, Al Haq; Wahyu Wibowo, Febrian; Yunadi, Ahmad (Journal of Islamic Economic and Law (JIEL), 2025)
The increasing awareness of the Muslim community on the importance of halal products encourages the need for assurance of halal aspects in food and beverage consumption, especially in tourist areas such as the Yogyakarta Palace. In this context, halal literacy, halal certification, information on ingredients, and product quality are important factors that influence consumer purchasing decisions. This study aims to analyze the influence of halal literacy, halal certification, ingredients, and product quality on purchasing decisions for food and beverage (F&B) products among visitors to the Yogyakarta Palace Tourism Complex. The background of this study is based on the importance of fulfilling halal aspects in the consumption of Indonesian Muslim society, especially in the era of globalization that demands caution in choosing food and beverage products. The research method used is quantitative with data collection techniques through questionnaires to 100 respondents. Data were analyzed using multiple linear regression and classical assumption tests through SPSS software. The results of the study showed that simultaneously, the four independent variables had a significant effect on purchasing decisions. Partially, the variables halal literacy, halal certification, and product quality had a positive and significant effect, while the ingredients variable showed an insignificant effect. This study provides important implications for business actors and certification institutions to improve consumer education and ensure the clarity and authenticity of halal certification on F&B products.